Examination of basic motor skills in children and adolescents - Soner Karadeniz; Ceren Suveren; Yasin Arslan; Tebessüm Ayyıldız Durhan; Tülay Ceylan; Faruk Albay; Hamza Küçük; Levent Ceylan (Frontiers in Physiology, 2024)
Aim of the study: The aim of this study was the investigation of basic motor skills in 5–14-year-old boys and girls.Materials and Methods: A total of 842 primary school children, 421 boys and 421 girls, participated in the study. 13.3% of the participants were 5–6 years old, 29.5% were 7–8 years old, 21.5% were 9–10 years old, 16.4% were 11–12, and 19.4% were 13–14 years old. The balance skills of the participants were measured with the (Körperkoordinationstest für Kinder) KTK test.Findings: When the classification of children according to KTK defining classes is examined, 40.7% are very good. When the children’s KTK Backward Balancing scores were examined, a statistically significant difference was found between gender and age groups (p < 0.05). Girls between the ages of 5–6 and 7–8 years had a higher score for KTK backward balance. KTK Total scores were examined according to the Body Mass Index groups, when the total scores of KTK were compared, the lowest scores were in the obese group.Conclusion: According to the study results, age is an essential factor for balance skills. As the age increased, the overall scores of the KTK increased. It was determined that girls’ KTK backward balancing scores were higher than boys. According to BMI results, the balance performances of obese children were found to be lower than the other groups. This difference can be explained by the negative effect of obesity in this age group. According to these results, it may be recommended to observe and improve the balance performances of obese children.